Sistem Pendukung Keputusan Penerima JAMKESMAS Metode AHP - Prihartanto, Lelono; , Muhammad Kusban, S.T, M.T (2016)
Data poor families is very influential on the recipient government systems. Poor data collection system is very accurate in using CMS so that no mutually agreed to accept the result of the decision. DSS is a system that is very helpful in determining the headman poor families in getting help, SPK used by AHP method. AHP is a flexible system in the determination and calculation of the highest priority. AHP calculation method using pairwise matrix system. This system is very accurate in the calculation of seeking the highest value in the determination JAMKESMAS receiver. Poverty criteria is based on the condition of village residents in the form of job Sidoharjo (PNS, Private, unemployment), House (decent, Pretty decent, less worthy, not worthy), Income (500,000, <Rp.1000.000, <Rp.2.000. 000,> Rp.2000.000), and the number of bears (1, 2, more than 2), Results of testing old system to the new system tedapat difference, to filter out as many as seven families or 19% of the actual eligible for assistance and 81% stated not eligible for assistance from 36 families. This system is useful in decision making for the aid recipients Sidoharjo village headman.